The myrmecofauna (Hymenoptera: Formicidae) of Iceland. Diversity and distribution of alien ants - Marco Mancini 1983- (2022)
Most of the Icelandic flora and fauna had to colonize the island after the last glacial period. Human colonization, and the subsequent increase in travel, horticulture and global trade, enabled alien species to settle in Iceland, including social hymenopterans. In the last decades a few alien ant species have been documented in Iceland, but knowledge about which species and their distribution is lacking. To study the myrmecofauna in Iceland, specimen records from > 700 sites were compiled. Analyzed were 634 records collected by the Icelandic Institute of Natural History (1974-2020) and by engaging the public and pest management professionals in and around Reykjavík 68 new records were collected (2019-2022). In total, representatives of 25 ant species were found. The most common indoor ants were Hypoponera punctatissima (546 records) and Monomorium pharaonis (42). One subterranean species, Hypoponera ergatandria (28), occurred both indoors and outdoors in geothermal areas. Hypoponera eduardi (4) was only present in geothermal areas. Lasius niger (34) was the only species commonly found outdoors, away from heated buildings. Sixteen species were found only once or twice indoors or in recently imported plant material. Overall, 24 ant species were presumed alien to Iceland, and one may be cryptogenic. The majority of species are (a) recent colonizers and (b) linked to the urban environment. Also, summarized are data on H. ergatandria, H. eduardi, L. niger, and Myrmica rubra cases in Iceland, with management recommendations and proposed research priorities. This study provides knowledge on the spread of alien and invasive ants in subarctic environments. Studies assessing the potential impacts of alien ants on Icelandic biomes are needed. Nær öll flóra og fána Íslands nam land eftir að síðasta jökulskeiði lauk. Frá landnámi og vegna aukningar í ferðalögum, innflutningi varnings og plantna til landsins á síðustu árum, hefur framandi tegundum tekist að nema hér land, þar á meðal félagsskordýrum af ætt æðvængja. Á ...